2018
DOI: 10.2967/jnmt.117.204933
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT Can Predict Development of Thyroiditis Due to Immunotherapy for Lung Cancer

Abstract: Our primary purpose was to determine whether increased F-FDG uptake in the thyroid gland predicts development of thyroiditis with subsequent hypothyroidism in patients undergoing immunotherapy with nivolumab for lung cancer. Secondarily, we determined whetherF-FDG uptake in the thyroid gland correlates with number of administered cycles of nivolumab. Retrospective chart review over 2 y found 18 lung cancer patients treated with nivolumab who underwentF-FDG PET/CT before and during therapy. SUV, SUV, and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…Patients with increased 18 FDG uptake in the thyroid before ICI-treatment could have an increased risk for developing/worsening TDs ( 61 ). Higher 18 FDG uptake could be correlated with the severity of hypothyroidism and TgAb positivity ( 63 ) and might predict the development of thyroiditis with subsequent hypothyroidism ( 83 ).…”
Section: Immune Checkpoint Inhibitor-induced Thyroid Disordersmentioning
confidence: 99%
“…Patients with increased 18 FDG uptake in the thyroid before ICI-treatment could have an increased risk for developing/worsening TDs ( 61 ). Higher 18 FDG uptake could be correlated with the severity of hypothyroidism and TgAb positivity ( 63 ) and might predict the development of thyroiditis with subsequent hypothyroidism ( 83 ).…”
Section: Immune Checkpoint Inhibitor-induced Thyroid Disordersmentioning
confidence: 99%
“…In NSCLC patients, the most common irAEs are rash and diarrhea with nivolumab treatment and hypo-and hyperthyroidism with pembrolizumab treatment [153]. In particular, thyroiditis has an incidence of 5-23%, and [18F]FDG uptake in the thyroid gland can depict thyroid inflammation even before laboratory changes are observed and allows the prediction of thyroid dysfunction development, as demonstrated by the study by Eshgh et al [154], which was performed on 18 patients with NSCL and who were treated with nivolumab. Interestingly, it has been recently shown that the onset of irAEs may also predict the clinic benefit of ICIs [155][156][157].…”
Section: [18f]fdg and Immune-related Adverse Events (Iraes)mentioning
confidence: 99%
“…In NSCLC patients, the most common irAEs are rash and diarrhea with nivolumab treatment and hypo-and hyperthyroidism with pembrolizumab treatment [141]. In particular, thyroiditis has an incidence of 5%-23% and [18F]FDG uptake in the thyroid gland can depict thyroid inflammation even before laboratory changes are observed and allows prediction of development of thyroid dysfunction, as demonstrated by the study of Eshgh et al [142], performed on 18 patients with NSCL and treated with nivolumab. Interestingly , it has been recently shown that the onset of irAEs may also predict ICIs clinical benefit [143][144][145].…”
Section: [18f]fdg and Immune-related Adverse Events (Iraes)mentioning
confidence: 99%